Oral cancer awareness among patients attending university dental clinic in Kuantan, Pahang - Abllah, Zurainie; Juhari, Sofiah; Ahmad Pauzi, Nasuha; Tin, Myo Han; Hassan, Haszelini; Faisal, Ghasak Ghazi (Elsevier, 2019)
In Malaysia oral cancer is the 21st most common cancer in general population. It is 17th most common cancer in male and 16th most common cancer in female. The incidence of oral cancer is predominant among Indian ethnic group where mouth and tongue cancer were among most 10 most cancer for both male and female The study is to assess the awareness of dental patients on oral cancer and its relation to their socio-demographic background. Questionnaires were distributed to the 100 participants to assess their awareness on oral cancer in a university dental clinic in Kuantan, Pahang. Cross analysis, t-test and ANOVA tests were applied to infer the relationship between socio-demographic and awareness level of the respondents. There was a trend for young, good education and income with good awareness about oral cancer, but not significant associated with socio-demographic. The awareness levels of the participants are low and not significantly influenced by socio-demographic status.